LOCALIZATION OF NON-INTERACTING FIELDS IN A MODIFICATION OF CONFORMALLY FLAT 5-DIMENSIONAL BRANEWORLD MODEL - Taufiqur Rohman, Muhammad
A modification of the Randall-Sundrum metric model in the form of conformally flat metric was proposed some years ago. The proposed model shows better localization properties than the original Randall-Sundrum model. However, this new model still does not meet the expectation that all fundamental fields can be localized for one type of warp factor, e.g. for a decreasing warp factor. In this research we propose to add a factor ????(????) in the extra coordinate part of the above modified Randall-Sundrum metric, and add a factor ????(????) in the whole coordinates, then derive conditions for localization for scalar and vector fields. ???? is the extra coordinate. We then look for some functions ????(????) that fulfill the localization conditions for both scalar and vector fields. Examples of the function f(r) under investigation are ????????????(????????), ????????????(????????+????????2), ????????????(????/????), ????????, ????????+????????2, and ?????????????????????.